The Influence of Leadership Style, Organizational Culture, and Work Environment on Turnover Intention at PT. Mandala Multifinance, Palu Branch - Rahman, Abd.; A, Muhammad Umar; Yasin, Muhammad; Rezal, Muhammad; Sangkota, Megawaty; Azis, Abd. (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2025)
This study aims to examine the extent to which the influence of leadership style (LS), organizational culture (OC), and work environment (WE) on the turnover intention (TI) of employees of PT. Mandala Multifinance. The assumption is that these three variables are one of the factors causing many employees to leave the company. The company cannot ignore these causal factors because they can affect the comfort of employees, which ultimately affects their desire to leave the company. This research involved 115 employees of PT. Mandala Multifinance and tested quantitatively using SPSS version 22. This study's calculated results indicate a partial positive influence on LS and OC variables, while the WE variable does not. Simultaneous calculation results show a positive influence of the three variables on turnover intention. In the competitive landscape of the financial services industry, where employee retention is critical to maintaining service quality and client trust, understanding these factors is essential. High turnover can disrupt client relationships and increase recruitment and training costs, making it imperative for organizations to address leadership, culture, and environmental factors effectively. This study suggests that all companies, particularly in the financial sector, pay attention to these factors for the convenience of employees to reduce turnover intention.